2012
DOI: 10.2996/kmj/1333027261
|View full text |Cite
|
Sign up to set email alerts
|

The Nash problem of arcs and the rational double point E6

Abstract: This paper deals with the Nash problem, which consists in proving that the number of families of arcs on a singular germ of a surface S coincides with the number of irreducible components of the exceptional divisor in the minimal resolution of this singularity. We propose a program for an affirmative solution of the Nash problem in the case of normal 2-dimensional hypersurface singularities. We illustrate this program by giving an affirmative solution of the Nash problem for the rational double point E 6 . We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 24 publications
0
12
0
2
Order By: Relevance
“…On the other hand, bijectivity of the Nash mapping has been shown for many classes of surfaces (see [6], [10], [8], [9], [12], [13], [17], [19], [20], [21], [22], [24], [25], [26]). The techniques leading to the proof of each of these cases are different in nature, and the proofs are often complicated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, bijectivity of the Nash mapping has been shown for many classes of surfaces (see [6], [10], [8], [9], [12], [13], [17], [19], [20], [21], [22], [24], [25], [26]). The techniques leading to the proof of each of these cases are different in nature, and the proofs are often complicated.…”
Section: Introductionmentioning
confidence: 99%
“…The techniques leading to the proof of each of these cases are different in nature, and the proofs are often complicated. It is worth noting that even for the case of the rational double points not solved by Nash, a complete proof had to be awaited until 2010; see [19], where the problem is solved for any quotient surface singularity, and also [21] and [24] for the cases of D n and E 6 . In [4] it is shown that the Nash problem for surfaces only depends on the topological type of the singularity.…”
Section: Introductionmentioning
confidence: 99%
“…Étant donné explicitement une variété V et une désingularisation π, on remarque que déterminer si une composante irréductible de la fibre exceptionnelle de π est ou non un diviseur essentiel reste un problème difficile. L'approche de Nash est donc très De nombreux mathématiciens, qu'on ne peut pas tous citer ici, ont apporté de nouvelles contributions originales à l'étude du problème de Nash, surtout dans le cas de variétés de dimension 2 et 3 (voir par exemple [LJ80], [Reg95], [GSLJ97], [LJRL99], [IK03], [Ish05], [Ish06], [PPP06], [GP07], [Mor08], [Plé08], [PPP08], [Pet09], [LA11], [FdB12], [PS12], [dFD14]). …”
Section: Introductionunclassified
“…Despite these advances, up to the moment of writing this article, the Nash problem was still open for the very basic cases of surface rational double points E 6 , E 7 and E 8 (an independent proof for E 6 was found by Plénat and Spivakovsky in [30]). Some time after this work, in [6], the author and Fernández de Bobadilla managed to prove the bijectivity of the Nash map in…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in [18] it is proved that divisors that are not uniruled are in the image of the Nash map and that the so-called lifting wedge property for the case of quasi-rational surfaces would imply that the surjectivity of the Nash map for normal surface singularities. In [5], it is proved that the Nash problem for surfaces only depends on the topological type of the surface singularity and that a positive answer for the case of rational homology sphere links implies a positive answer for any normal surface; in [5,18,33] certain characterizations of the bijectivity of the Nash mapping are proved in terms of uniparametric families of arcs.Despite these advances, up to the moment of writing this article, the Nash problem was still open for the very basic cases of surface rational double points E 6 , E 7 and E 8 (an independent proof for E 6 was found by Plénat and Spivakovsky in [30]). Some time after this work, in [6], the author and Fernández de Bobadilla managed to prove the bijectivity of the Nash map in…”
mentioning
confidence: 99%